Amul - 2014 - Dixit, Mukund R., (SAGE knowledge. Cases., 2016)
This case describes the challenges faced by Amul in organising the dairy farmers into a co-operative and creating continuous opportunities for value additions. The participants are required to review the developments in the organisation and recommend a future strategy.